Evaluasi Pengelolaan Sampah terpadu melalui Analisis Skenario dengan Pendekatan Waste Reduction Model V.16 (Studi Kasus TPA Makbon, Sorong, Provinsi Papua Barat Daya) - Fadlil, Firmanullah; Difinubun, Yusron; Goa, Yusnita La; Rahman, Ainul Alim (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
The production of municipal solid waste is a global problem, therefore due to the large amount and environmental impacts produced, urban solid waste needs to be managed properly. The implementation of more appropriate and efficient solutions is important for sustainable development, minimizing environmental impacts and saving energy. This study aims to analyze alternative scenarios using the Waste Reduction Model (WARM) V.16 to find the best solution for solid waste management in Sorong City. Existing Scenarios, Scenario 1 (50% landfill, 25% incineration, 25% recycle), Scenario 2 (25% landfill, 50% incineration, 25% recycle) and Scenario 3 (25% landfill, 25% incineration, 50% recycle) are implemented using the WARM V.16 model. The results of this study indicate that Scenario 3 provides the best results in terms of environmental impact and energy savings (-30,443.37 MTCO2e and -784,554.96 MBTU), followed by Scenario 2 (-10,146.07 MTCO2e and -553,413.70 MBTU), Scenario 1 (-1,649.74 MTCO2e and -441,080.90 MBTU), and the Existing Scenario (35,640.31 MTCO2e and 13,725.96 MBTU).